Serological response to lumpy skin disease in recovered and clinically healthy vaccinated and unvaccinated cattle of Bangladesh - Parvin, Rokshana; Al Mim, Sirat; Haque, Md. Nurul; Jerin, Israt; Nooruzzaman, Mohammed; Hossain, Md. Riabbel; Chowdhury, Emdadul Haque; Globig, Anja; Knauf, Sascha; Tuppurainen, Eeva (Frontiers in Veterinary Science, 2025)
Lumpy skin disease (LSD) is one of the most economically important transboundary animal diseases that emerged in Bangladesh in 2019. It has a significant economic impact on household cattle owners in rural settings in Bangladesh. A cross-sectional study was undertaken in selected areas of the Mymensingh districts of Bangladesh between July 2021 and May 2023. A total of 1,161 blood samples were collected from 105 households and four herds comprising 904 and 257 cattle, respectively. The presence of LSD virus (LSDV) antibodies in serum was detected using enzyme-linked immunosorbent assay (ELISA). The overall seroprevalence of LSD in the study area during the sampling period was 26.2% (n = 304/1,161; 95% confidence interval: 4.90–10.20). Based on the disease status, the seroprevalence of the recovered animal was 40.07%, significantly higher than that of unvaccinated animals that had been in contact with affected cattle but never showed any visible clinical signs of LSD (23.27%), and the seroprevalence in cattle that were showing clinical signs when serum samples were collected (18.0%). Nonetheless, seroconversion in the vaccinated population lasted 6–12 months after vaccination, and animals that recovered natural infection also exhibited measurable seroconversion up to 6 months after exposure. The study demonstrated the seroprevalence of LSD in cattle kept in rural Bangladeshi households and the duration of antibody responses in animals recovered from natural LSD infection, cattle that were clinically healthy but had circulating LSDV in the herd, and animals vaccinated with vaccines containing goat pox virus or attenuated LSDV. The results of this study help in defining an effective and feasible vaccination strategy considering the duration of immunity after vaccination or natural LSD infection.